# Thread: Solving by Quadratic Formula

1. ## Solving by Quadratic Formula

I know the formula but I this problem seems to be wrong when I solve it.

m^2+5m-6=0

a=m
b=5
c=-6

x=-5+-√5^2-4(M)(-6) over 2(M)

So I get -5+-√25-24/2

-5+-√1/2
-5+1/2=-2 or -5-1/2=-3

That is what I got however the answer is suppose to be -6 and 1... Just wondering where I went wrong.

2. ## Re: Solving by Quadratic Formula

Originally Posted by Past45
I know the formula but I this problem seems to be wrong when I solve it.

m^2+5m-6=0

a=m
b=5
c=-6

x=-5+-√5^2-4(M)(-6) over 2(M)

So I get -5+-√25-24/2

-5+-√1/2
-5+1/2=-2 or -5-1/2=-3

That is what I got however the answer is suppose to be -6 and 1... Just wondering where I went wrong.
a is the number that the square term is multiplied by. In this case, a = 1, not m.

3. ## Re: Solving by Quadratic Formula

Right, but it it still is going to have those same numbers when you solve them.

4. ## Re: Solving by Quadratic Formula

$m^2+5m-6=0$

$m = \frac{-5 \pm \sqrt{5^2 - 4(1)(-6)}}{2}$

try again ... pay close attention to your signs

5. ## Re: Solving by Quadratic Formula

Got it! Thanks.